2021
DOI: 10.1016/j.virusres.2021.198484
|View full text |Cite
|
Sign up to set email alerts
|

A novel RdRp-based colorimetric RT-LAMP assay for rapid and sensitive detection of SARS-CoV-2 in clinical and sewage samples from Pakistan

Abstract: Novel corona virus SARS-CoV-2, causing coronavirus disease 2019 (COVID-19), has become a global health challenge particularly for developing countries like Pakistan where overcrowded cities, inadequate sanitation, little health awareness and poor socioeconomic conditions exist. The SARS-CoV-2 has been known to spread primarily through direct contact and respiratory droplets. However, detection of SARS-CoV-2 in stool and sewage, have raised the possibility of fecal-oral mode of transmission. Currently, quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…As shown in Figure 2a, our LAMP assay was able to successfully detect as low as 100 starting copies of extracted vRNA. We have previously demonstrated that the LAMP primers used in this report can potentially detect as low as 10 copies of synthetic target in the presence of 1 mg/mL bovine serum albumin [18] Melt curve analysis also showed sharp peaks around 82 • C for all the concentrations (Figure 2b). In order to demonstrate the specificity of our LAMP assay in targeting SARS-CoV-2 specific sequences compared to two closely related coronaviruses, SARS-CoV and MERS-CoV controls were also included.…”
Section: Sars-cov-2 Specific Lamp Assay Using Conventional Thermocyclermentioning
confidence: 50%
See 1 more Smart Citation
“…As shown in Figure 2a, our LAMP assay was able to successfully detect as low as 100 starting copies of extracted vRNA. We have previously demonstrated that the LAMP primers used in this report can potentially detect as low as 10 copies of synthetic target in the presence of 1 mg/mL bovine serum albumin [18] Melt curve analysis also showed sharp peaks around 82 • C for all the concentrations (Figure 2b). In order to demonstrate the specificity of our LAMP assay in targeting SARS-CoV-2 specific sequences compared to two closely related coronaviruses, SARS-CoV and MERS-CoV controls were also included.…”
Section: Sars-cov-2 Specific Lamp Assay Using Conventional Thermocyclermentioning
confidence: 50%
“…Our previous in silico analysis showed that the region targeted in our LAMP assay is not only conserved across various isolates and variants, but also it is highly specific for SARS-CoV-2. Our LAMP primers did not show any significant similarity with the genomes of any of the six closely related human coronaviruses [18].…”
Section: Performance Of Portable Device For Lamp Based Detection Of Sars-cov-2mentioning
confidence: 77%
“…In order to verify that the fluorescent signal observed in our LAMP in the core-shell bead assay is from the specific amplification of the target, and to study the effect of possible non-specific amplification on the overall fluorescence signals, we carried out a control LAMP reaction with non-specific primers. The so-called “unrelated primers control” (UPC) reaction used Met-5A total RNA as a template, and a primer set which was not targeted against any human gene ( Table 2 ) [ 32 ]. As indicated in Figure 3 d, the background fluorescence signal from the non-specific dsDNA molecules generated during the LAMP reaction was less than 6% of the maximum fluorescence signal obtained from the positive sample, and it is negligible to be considered as negative.…”
Section: Resultsmentioning
confidence: 99%
“…The standard PCR amplification requires a bulky thermal cycler, cycling in multiple temperature steps between 60 °C and 95 °C, and a long reaction time (≥90 min), which is unsuitable for on-site detection. From Table 2 , LAMP and RPA technologies are the most used amplification methods, which play a vital role in the clinical detection and field application of nucleic acids ( Han et al, 2020b ; Haque et al, 2021 ). Compared with conventional PCR, LAMP has the advantages of higher sensitivity, shorter reaction time, and simple operation ( Gunasegar & Neela, 2021 ).…”
Section: Challenges and Prospectsmentioning
confidence: 99%